Back Cover: TCNQ Interlayers for Colloidal Quantum Dot Light‐Emitting Diodes (ChemPhysChem 8/2016). Issue 8 (5th April 2016) - Koh, Weon‐kyu; Shin, Taeho; Jung, Changhoon; Cho, Dr‐ Kyung‐Sang
Abstract : 7, 7, 8, 8‐Tetracyanoquinodimethane (TCNQ) interlayers improve the electroluminescence performance of colloidal quantum dot light‐emitting diodes, owing to improved charge injection through the charge‐transfer complex of TCNQ/ZnO. More information can be found in the Communication by W.‐k. Koh et al. onpage 1095 in Issue 8, 2016 (DOI:10.1002/cphc.201600054 ).